Simulation Analysis of Vibration and Noise Characteristic of Rocket Artillery Elevating Mechanism Planetary Reducer - Li Zhigang; Wang Zhengyao (Jixie chuandong)
For a rocket artillery elevating mechanism planetary reducer,firstly the rigid dynamics model is built by using the software ADAMS and the rightness of the model is verified through dynamics simulation,then,the dynamic load in time- domain and frequency- domain for the key parts of the reducer are obtained.Secondly,the finite element modal of the reducer box is established and the forced vibration response of the reducer is calculated with the software LMS Virtual. Lab and its vibration noise characteristics is simulated by using the acoustic boundary element method. A foundation for further understand the dynamic performance of the rocket artillery elevating mechanism reducer is provided,and the technical support for the optimal design of vibration and noise reduction of this sort of reducer is also provided.